Hybrid Models with Technology: Is it Effective for Learning in Abnormal Situations? - Purba, Ramen Antonov (Journal of Education Reseach and Evaluation, 2022)
In the Covid-19 pandemic situation, lecturers use non-uniform technology. They are using WhatsApp, Google Classroom, and social media such as Facebook and Youtube. The results of all observations are not optimal. The research will combine a hybrid model, namely a blended learning model with problem-based learning and Sevima EdLink. Will see blended learning with problem-based learning and whether Sevima EdLink can improve learning outcomes and problem-solving capabilities. Research quasi-experimental design. Research at the Politeknik Unggul LP3M Informatics Management study program, the total population of 4th-semester students is 54. They are collecting data using question fields and exams. Analysis using t-test. They were followed by normality tests, homogeneity, and hypothesis. Learning with the hybrid model is going well. Research shows that blended learning with problem-based learning and Sevima EdLink runs on a reasonable classification composition. There was a very positive and contextual effect of combining blended learning with problem-based learning and Sevima EdLink on learning outcomes. There was also a very positive and contextual effect of combining blended learning with problem-based learning and Sevima EdLink on problem-solving capabilities. Research also shows that combining blended learning with problem-based learning and Sevima EdLink is reasonable and appropriate for use in abnormal learning situations.